2014
DOI: 10.1186/1755-7682-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected triggers for pheochromocytoma-induced recurrent heart failure

Abstract: Pheochromocytoma crisis typically presents as paroxysmal episodes of headache, tachycardia, diaphoresis or hypertension. We describe an uncommon case of recurrent non-hypertensive heart failure with systolic dysfunction in a young female due to pheochromocytoma compression. It presented as acute pulmonary oedema while straining during pregnancy and later on as cardiogenic shock after a recreational body massage. Such crisis occurring during pregnancy is rare. Moreover, of the few reported cases of pheochromocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Previous reports have showed that pheochromocytoma-induced cardiomyopathy can be reversed with medical therapy first followed by a subsequent tumor extirpation [ 4 , 6 9 ], as with our patient. The prognosis of catecholamine-induced cardiomyopathy depends on early diagnosis and prompt medical and surgical treatment.…”
Section: Discussionsupporting
confidence: 78%
“…Previous reports have showed that pheochromocytoma-induced cardiomyopathy can be reversed with medical therapy first followed by a subsequent tumor extirpation [ 4 , 6 9 ], as with our patient. The prognosis of catecholamine-induced cardiomyopathy depends on early diagnosis and prompt medical and surgical treatment.…”
Section: Discussionsupporting
confidence: 78%
“…The clinical presentation is variable: hypertension is the most frequent (65%), and the classical triad (headache, palpitations, and diaphoresis) is described in 4% ( 1 ). There are few reports of patients who present cardiogenic shock ( 2 ), but the predominance of multiorgan failure over catecholamine excess symptoms is frequently described ( 1 ). In this case, dobutamine could contribute to the evolution because of its potential to induce shock in patients with pheochromocytoma ( 2 ).…”
mentioning
confidence: 99%
“…There are few reports of patients who present cardiogenic shock ( 2 ), but the predominance of multiorgan failure over catecholamine excess symptoms is frequently described ( 1 ). In this case, dobutamine could contribute to the evolution because of its potential to induce shock in patients with pheochromocytoma ( 2 ). The pheochromocytoma resection is associated with improvement of ventricular function in 96% of cases.…”
mentioning
confidence: 99%